Notice of the Brochs or Round Towers of Orkney, with Plans, Sections, and Drawings, and Tables of Measurements of Orkney and Shetland Brochs (Proceedings of the Society of Antiquaries of Scotland, 1872)
[The journal notes that this paper was read on 11 June 1866 and will be published in the Archaeologia Scotica.]